2008
DOI: 10.1002/chem.200800719
|View full text |Cite
|
Sign up to set email alerts
|

Hexa‐ and Dodecanuclear Polyoxomolybdate Cyclic Compounds: Application toward the Facile Synthesis of Nanoparticles and Film Electrodeposition

Abstract: Two new compounds based on O(3)PCH(2)PO(3)(4-) ligands and {Mo(V)(2)O(4)} dimeric units have been synthesized and structurally characterized. The dodecanuclear Mo(V) polyoxomolybdate species in (NH(4))(18)[(Mo(V)(2)O(4))(6)(OH)(6)(O(3)PCH(2)PO(3))(6)] x 33 H(2)O (1) is a cyclohexane-like ring in a chair conformation with pseudo S(6) symmetry. In the solid state, the wheels align side by side, thus delimiting large rectangular voids. The hexanuclear anion in Na(8)[(Mo(V)(2)O(4))(3)(O(3)PCH(2)PO(3))(3)(CH(3)AsO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 37 publications
5
39
0
1
Order By: Relevance
“…and Pd 4? states are 335 and 340.6, 337.5 and 342.9, and 338.4 and 343.5 eV, respectively corresponding to the 3d 5/2-3/2 spin-orbit doublet [33][34][35][36]. The binding energy of Zr 3p also falls in the same range.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 82%
“…and Pd 4? states are 335 and 340.6, 337.5 and 342.9, and 338.4 and 343.5 eV, respectively corresponding to the 3d 5/2-3/2 spin-orbit doublet [33][34][35][36]. The binding energy of Zr 3p also falls in the same range.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 82%
“…The data revealed the tetraoxo 2+ bridging structure found in many compounds. [44,[45][46][47][48] The anionic Tpms group acts as a tridentate N,N,O ligand. The basal positions in each octahedron are occupied by the N11 and N14 atoms and the bridging O2 oxygen atoms and the two distorted octahedra share the common O2-O2 i edge; the apical positions are taken up by the oxido O1 and O12 atoms from the sulfonate group.…”
Section: Reactions Of Li[mo(tpms)(co) 3 ] (1) With Imentioning
confidence: 99%
“…Moreover, such nanosystems are obtained in a one-pot procedure, in water, at room temperature and without any additional surfactant. For example, by simply mixing the cyclohexanelike dodecanuclear compound mentioned above and Pd II cations in aqueous solution, NPs with diameter of 9-14 nm containing a Pd 0 core and capped by POMs are obtained [6]. Additionally, it has also been shown that Ag 0 [9] and Pt 0 [10] POM capped NPs can be obtained using this procedure.…”
Section: Introductionmentioning
confidence: 96%
“…A larger complex, a dodecanuclear wheel which adopts a cyclohexane-like ring in a chair conformation has been obtained in absence of any additional coordinating groups. Nevertheless, the presence of ammonium cations in the reacting medium is crucial for the obtaining of this species, highlighting the importance of the nature of the counterions on the resulting POM [6]. In addition to these cyclic systems, bicyclic compounds have also been obtained.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation